Improvement of drying process of beer pellet in the fluidized bed apparatus - Pohozhayev, Alexander; Yakobchuk, Roman (My University, 2014)
Introduction. It is appropriate to model and calculate the processes in the fluidized bed apparatus using computer simulation techniques and experimental studies in order to improve the drying process of beer pellet and develop new structures of dryers. Materials and methods. The process of drying spent grains in the fluidized bed dryer screw. Beer pellet has a thick consistency of rough grinding grain product, a light brown color, sweet flavor and malt smell and it rich in nutrients. Simulation of beer pellet drying was based on the finite element method using the software package Flow Vision and mathematical and statistical methods. Results and discussion. The mathematical model determining allow the coolant pressure in the drying chamber, to depend on the speed and coolant gas distribution device design and optimum conditions of drying installation. Uniform heating and drying the product in the fluidized state at any point of intersection of the drying chamber of screw dryer is achieved through high-quality distribution of coolant above gas distribution device. The expediency of Reynolds criterion definition was proved using semi-empirical interpolation formula derived by V. Goroshko, L. Rosenbaum, and O. Todes. It allows reducing of marker dimensions of the dryer. The design of screw dryers was improved by established under the perforated gas distribution grid profile that provides directional movement of coolant and coolant levels the pressure along the length of the drying chamber. Conclusions. Using the results of research for select the mode of drying in the design phase of drying equipment allows improve drying process beer pellet in the dryer.
Keywords: beer; pellet; drying; screw; дробина; сушіння; шнек; пиво; дробина; сушка; кафедра технологічного обладнання та комп’ютерних технологій проектування